The Effect of Training using Hand Paddles on the Speed of Freestyle Swimming in Beginners at the USC Club - Genta, Genta Dwi Putra; Anton, Anton Komaini (UNIB Press, 2023)
This study aims to determine the effect of hand paddle training on freestyle swimming speed for beginners at the USC Club. This research is a quasi-experimental research, in this experimental research, the sample used was 20 people who were novice athletes in the USC club. The instrument used in this study was the 25 meter freestyle swimming test. Based on the results of research and discussion, it concludes that the effect of using a hand paddle on the speed of freestyle swimming for beginners in the club states that the final test with tcount 3.905 from the results of the t test, the test results tcount > ttable with a significant level = 0.05 with a value of ttable 1.734 means that there is a significant effect between training using hand paddles on the speed of freestyle swimming in beginner athletes at the USC club.